ENHANCING STUDENTS READING SKILL BY USING RECIPROCAL TEACHING - FITRI WIJAYANTI; RIYANI RIYANI (English Education Department Slamet Riyadi University Surakarta, 2020)
The aims of the study are to find out (1) whether Reciprocal Teaching can improve the students reading skill at the eighth grade of SMP PGRI 1 Surakarta in 2019/2020 academic year, (2) the class condition when Reciprocal Teaching is applied in the classroom to teach reading skill in SMP PGRI 1 Surakarta in 2019/2020 academic year. This research was carried out at SMP PGRI 1 Surakarta. The result of the research showed that Reciprocal Teaching can improve students’ reading skill of the students at grade VIII-A of SMP PGRI 1 Surakarta. The research was carried out in 2 cycles. In all cycle focused on a Descriptive text. The improvements can be seen from the students’ reading skill achievement. The mean score results of pre test was 42.57, post test 1 68.29, post test 2 79.00. The class condition was more conducive because the students paid attention to the researcher, the students were enthusiastic and interested to discuss within their group, the students were high concentration to the material, and the students were more active in the classroom. It can be concluded that the use of Reciprocal Teaching can improve the students reading skill in SMP PGRI 1 Surakarta in 2019/2020 Academic Year. Keywords: Reciprocal Teaching, Reading Skill, Descriptive Text, Classroom Action Research.